Дослідження верхньопалеолітичної стоянки Дорошівці ІІІ - Кулаковська, Л.; Усик, В.; Езартс, П.; Рідуш, Б.; Герасименко, Н.; Проскурняк, Ю. (Кам’яна доба України, 2011)
Стаття присвячена публікації матеріалів багатошарової стоянки Дорошівці ІІІ у Середньому Подністров'ї. Наводяться результати комплексних досліджень (геологія, геоморфологія, палеонтологія, палінологія та археологія). In the article represented previous results of investigations of the Dorochivzi III site where seven of Upper Paleolithic levels were discovered. On the base of technological and typological analysis these collections belong to the Gravettian techno-complex. The most rich from the archeological point of view cultural level 6 determined as variant of Gravettian with shouldered points.